Gradients of the intergenerational transmission of health in developing countries - Sonia Bhalotra; Samantha Rawlings (Institute for the Study of Labor (IZA), 2009)
This paper investigates the sensitivity of the intergenerational transmission of health to exogenous changes in income, education and public health, changes that are often delivered by economic growth. It uses individual survey data on 2.24 million children born to 600000 mothers during 1970-2000 in 38 developing countries. These data are merged with macroeconomic data by country and birth cohort to create an unprecedentedly large sample of comparable data that exhibit massive variation in maternal and child health as well as in aggregate economic conditions. The country-level panel is exploited to control for aggregate shocks and trends in unobservables within countries, while a panel of children within mother is exploited to control for family-specific endowments and neighbourhood characteristics. Child health is indicated by infant survival and maternal health by (relative) height. We find that improvements in maternal education, income and public health provision that occur in the year of birth and the year before birth limit the degree to which child health is tied to family circumstance. The interaction (gradient) effects are, in general, most marked for shorter women suggesting that children are more likely to bear the penalty exerted by poor maternal health if they are conceived or born in adverse socio-economic conditions.
Keywords: O12; I12; 330; Intergenerational transmission; early life conditions; health; infant mortality; height; growth; income; education; public health; gene; environment; in utero; Kinder; Gesundheit; Generationenbeziehungen; Lebensstandard; Mütter; Bildungsniveau; Gesundheitswesen; Entwicklungsländer